The Effect of the Animation Video Modeling Method on the Level of Knowledge of Mothers Training Toilet Training in Children Aged 2-3 Years in the Central Suwawa Health Center Area - Yulisti H. Igirisa; Sri A. Ibrahim; Cindy Puspita Sari Haji Jafar (Universitas Muhammadiyah Palu, 2026)
Toilet training is an important stage in toddler development that requires the readiness and knowledge of parents, especially mothers. However, many mothers still have limited knowledge about proper toilet training practices. This study aimed to analyze the effect of the animation video modeling method on the level of mothers’ knowledge in training toilet training for children aged 2–3 years in the Central Suwawa Health Center area. This research used a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The sample consisted of 48 mothers who had children aged 2–3 years, divided into an intervention group and a control group using cluster sampling. Data were analyzed using univariate analysis and the Independent Samples T-Test. The results showed that the average knowledge score of mothers in the intervention group increased from 6.95 before the intervention to 10.71 after receiving the animated video modeling method. Statistical analysis showed a significant effect with a p-value < 0.001. These findings indicate that the animation video modeling method is effective in improving mothers’ knowledge regarding toilet training in toddlers. Therefore, animated video-based health education can be recommended as an effective educational strategy in maternal and child health programs.